Intrauterine Growth Restriction: Cytokine Profiles of Trophoblast Antigen-Stimulated Maternal Lymphocytes - Raj Raghupathy; Majedah Al-Azemi; Fawaz Azizieh (Clinical and Developmental Immunology)
Intrauterine growth restriction (IUGR) is an important perinatal syndrome that poses several serious short- and long-term effects. We studied cytokine production by maternal peripheral blood lymphocytes stimulated by trophoblast antigens. 36 women with a diagnosis of IUGR and 22 healthy women with normal fetal growth were inducted. Peripheral blood mononuclear cells were stimulated with trophoblast antigens and levels of the proinflammatory cytokines IL-6, IL-8, IL-12, IL-23, IFNγ, and TNFα and the anti-inflammatory cytokines IL-4, IL-10, and IL-13 were measured in culture supernatants by ELISA. IL-8 was produced at higher levels by blood cells of the IUGR group than normal pregnant women, while IL-13 was produced at lower levels. IL-8, IFNγ, and TNFα were higher in IUGR with placental insufficiency than in normal pregnancy. IL-12 levels were higher and IL-10 levels were lower in IUGR with placental insufficiency than in IUGR without placental insufficiency. We suggest that a stronger pro-inflammatory bias exists in IUGR as compared to normal pregnancy and in IUGR with placental insufficiency when compared to IUGR without placental insufficiency. Several ratios of proinflammatory to anti-inflammatory cytokines also support the existence of an inflammatory bias in IUGR.